Synchronic variation in Sri Lanka Portuguese personal pronouns - Cardoso, Hugo C. (2021)
This paper presents and discusses the instances of synchronic variation attested in the personal pronoun paradigm of modern Sri Lanka Portuguese, an endangered Portuguese-based creole spoken by relatively small communities scattered across Eastern and Northern Sri Lanka. Although Sri Lanka Portuguese has a long history of documentation dating from, at least, the beginning of the 19th century, only a few studies have explicitly reported cases of synchronic variation. This study aims, therefore, to fill that gap, by contributing to the description and explanation of patterns of variation relating to the personal pronoun paradigm as encountered in documentary data collected between 2015 and 2020, over several field trips to the districts of Ampara, Batticaloa, Jaffna, and Trincomalee. The nature of the variation observed in the data ranges from phonetic alternations to strategies of paradigm regularization and stylistic shrinkage, often revealing the effects of diachronic processes of variant competition and substitution. Combining the observed patterns of variation with surveyed linguistic trends of language shift, we propose that obsolescence may be responsible for some of the variability encountered in modern SLP personal pronouns, especially that associated with certain socially- or geographically-defined subsets of the speech community (viz. the younger generations and the speakers from Jaffna) characterized by advanced language loss.